Unpacking grammatical errors in EFL descriptive texts: A multi-dimensional analysis of types, taxonomy, and underlying causes - Zulfikar, Zulfikar; Hasibuan, Apriyanti; Pulungan, Nurhajjah; Zulfikar, Teuku; Syafri, Mohamad (Universitas Islam Sultan Agung, 2025)
Grammatical accuracy remains a persistent challenge for EFL learners, particularly in descriptive writing, which demands precise language and structural control. This study investigated grammatical errors in a corpus of thirty descriptive texts produced by Indonesian high-school EFL learners, aiming to identify their types, classification, and underlying causes. Using a sequential explanatory mixed-methods design, errors were first identified through Azar’s coding system and classified using Bialystok et al.’s Surface Structure Taxonomy. Their causes were then interpreted through Corder’s and Ellis’ theoretical models, distinguishing intralingual from interlingual sources. Quantitative analysis showed singular-plural errors as the most frequent, followed by word choice, word form, and punctuation errors. Omission dominated misformation, addition and misordering, suggesting cognitive constraints or negative L1 transfer. Qualitative interpretation indicated that intralingual errors, comprising overgeneralization and simplification, significantly outweighed interlingual ones, highlighting the developmental nature of learners’ interlanguage at the intermediate level. The study underscores the need for clarification of complex grammatical structures, focused vocabulary development, the promotion of proofreading skills, and systematic feedback to address learners’ persistent difficulties in morphology, lexis, and mechanics. The insights gained from this analysis offer practical implications for improving writing curriculum design and instructional strategies.